Early Intervention Paraprofessional Standards: Development and Field Validation. (December 2017) - Banerjee, Rashida; Chopra, Ritu V.; DiPalma, Geraldine
Personnel standards are the foundations for how states and nations approve a program, engage in systemic assessment, and provide effective professional development to its early childhood professionals. However, despite the extensive use of paraprofessionals in early intervention/early childhood special education programs, there is a lack of national- and state-level guidance for training paraprofessionals. This article presents the process followed for development and validation of statewide personnel standards for paraprofessionals who work in early intervention settings and the results of this validation study. The development and validation process for these new knowledge and skills competencies followed the process used by Division for Early Childhood and the Council for Exceptional Children for development and validation of personnel standards and K-12 special education paraeducator professional development standards. Challenges, limitations, and future directions are discussed.